Yeha, Äthiopien: Die Restaurierungsarbeiten am Monumentalbau Grat Beʿal Gebri - Schnelle, Mike (e-Forschungsberichte des DAI, 2023)
Since 2009 the monumental building named Grat Beʿal Gebri has been investigated and restored concurrently in a cooperation project between local authorities and the Sanaa Branch of the DAI. The complex dates to around 800 BC and is therefore the oldest preserved timber-frame structure in Eastern Africa and the greatest roofed timber-frame structure in South Arabia and Eastern Africa. The restoration work and the protection of the building include capacity building measures involving local workers. In 2014 the restoration and protection work focused on the roofing of the south-western part of the structure using scaffold elements, on the restoration of timberframe walls and of an entrance, on the protection of wall copings and on the anastylosis of a part of the outer façade.